Los sistemas simbólicos en el poemario el fulgor de José Ángel Valente - Maldonado, Bernardita (2016)
The general objective of the present investigation entitled “The Symbolic Systems in the poetry collection El Fulgor by Jose Angel Valente”, analyze the aforementioned poetic set, based on the categorization of the symbols that configure its recurrent systems, which made it possible to determine the main traditions that form this collection. Another specific target is the interpretation of symbolic systems of El Fulgor. For the investigation the inductive-deductive method, the analytic-synthetic method, the historical method, the hermeneutical method and the bibliographic technique are used. The application of these methods and especially the inductive method allows inquiring the mystical traditions of the poem valentian. The hermeneutical procedure leads to the interpretation of the main symbologies presented in “El Fulgor” that were analyzed as an univocal and dialogic symbolic system expressed by an essential language, which refers to the sacredness of every human being. It is recommended to promulgate the valentian work, which opens the fieldof study more widely and diversely due to its characteristics.